Improving the overall environmental performance of existing telecommunications facilities. - Graedel, Thomas E. (The International Journal of Life Cycle Assessment)
Superior environmental performance has not traditionally been a goal of managers of telecommunications facilities, but there is now considerable pressure to go 'beyond compliance,' even for facilities that have been in existence for many years. In this regard, significant environmental improvement can be achieved by taking a life cycle perspective. We have conducted a streamlined life cycle assessment on two existing telecommunications facilities, one providing installation and maintenance services and the other network management services. With the results of this assessment as a basis, we propose a number of generic steps that can be taken to improve the environmental performance of most existing telecommunications facilities.